The Effect of The Optimum Performance Training Model on Increasing Agility In Female Futsal - Alya Insiyah Ukhti; Dikdik Zafar Sidik; Yudi Nurcahya (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
This study aims to evaluate the effect of the Optimum Performance Training (OPT) training model on improving anaerobic ability, especially in the aspect of agility in female futsal athletes of UKM UPI. The method used is ex post facto, where researchers cannot manipulate data. The research sample consisted of 9 female futsal athletes, and agility measurements were made using the shuttle run test. The pretest results showed an average value of 7.07 with a standard deviation of 0.32924, while the posttest showed an average value of 6.87 with a standard deviation of 0.43162. The minimum pretest value was 6.70 and the maximum was 7.60, while the posttest showed a minimum value of 6.20 and a maximum of 7.59. Hypothesis testing using the paired sample test resulted in a t value of 3.682 and a Sig. (2-tailed) value of 0.006, which indicates that H0 is rejected. Thus, it can be concluded that the application of the OPT training model has a significant effect on increasing agility in UPI female futsal players. This research provides an important contribution to the development of a more effective futsal training program to improve athlete performance.